Postoperative complications and long-term outcomes after total and subtotal thyroidectomy: a retrospective study - Sobhan Javidi; Sepehr Sadrizadeh; Ali Sadrizadeh; Shokoufeh Bonakdaran; Lida Jarahi (Scientific Reports)
Abstract The choice between total thyroidectomy (TT) and subtotal thyroidectomy (STT) can affect postoperative complications and long-term outcomes in these patients. This study aimed to investigate postoperative complications and long-term outcomes in patients who underwent TT and STT. This retrospective study investigated 1.022 patients who admitted to Ghaem and Razavi hospitals, Mashhad, and underwent thyroidectomy between 2011 and 2017. Data related to postoperative complications, recurrence rate and overall survival were collected and analyzed. The data collection tool used in this research was a checklist. In this study, women accounted for 863 and men for 159 of the total population. The highest number of thyroidectomy surgeries was found in 2013 and in all years the majority of thyroidectomy surgeries were performed on women. The results demonstrated that 71.2% of the patients underwent TT and 28.8% underwent STT. The percentage rate of recurrent laryngeal nerve injury after thyroidectomy surgery (regardless of the type of selected surgery) was 6.1%, affecting 62 individuals. No significant relationship was observed between the type of selected surgery and damage to this nerve (P > 0.05). In addition, a statistically significant correlation was reported between thyroidectomy and suffering from hypocalcemia (P < 0.05). The study revealed that TT was associated with a higher postoperative complication rate compared to STT. Individual treatment plans must be developed based on the risks and benefits of each surgical approach.